2018
DOI: 10.15547/bjvm.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phoenix dactylifera pollen grains extract supplementation on post-thaw quality of Arabian stallion semen

Abstract: -Nattat, 2018. Effects of Phoenix dactylifera pollen grains extract supplementation on post-thaw quality of Arabian stallion semen. Bulg. J. Vet. Med., 21, No 1,[40][41][42][43][44][45][46][47][48][49] This study explored the effect of extender supplementation with different concentrations of date palm pollen grain (DPPG) on post-thawed sperm motility, viability index, membrane and acrosome integrities in Arabian stallions. Five ejaculates from each of four Arabian stallions were subjected to cryopreservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
4
10
0
2
Order By: Relevance
“…DPP beneficial effect on spermatozoa could be attributed to its antioxidant properties (El-Sisy et al 2018) and its powerful free radical scavenging capacity (El-Kashlan et al 2015). Indeed, DPP seems able to protect sperm cells against oxidative damage (Agarwal and Rao 2000) by scavenging ROS through high content of polyphenols such as flavonoids (Wettasinghe and Shahidi 2000;Le Blanc et al 2009), vitamins C, B 1 , B 2 , E, nicotinic acid (Niacin) and vitamin A (Hassan 2011), carotenoids and phytosterols (Broadhurts 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP beneficial effect on spermatozoa could be attributed to its antioxidant properties (El-Sisy et al 2018) and its powerful free radical scavenging capacity (El-Kashlan et al 2015). Indeed, DPP seems able to protect sperm cells against oxidative damage (Agarwal and Rao 2000) by scavenging ROS through high content of polyphenols such as flavonoids (Wettasinghe and Shahidi 2000;Le Blanc et al 2009), vitamins C, B 1 , B 2 , E, nicotinic acid (Niacin) and vitamin A (Hassan 2011), carotenoids and phytosterols (Broadhurts 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Few in vitro studies have shown the beneficial effect of DPP extract supplementation to sperm extender in preserving and maintaining semen quality during cryoconservation especially in human, bulls buffalo and stallion (Al-Dujaily et al 2012;El-Sheshtawy et al 2014El-Sisy et al 2018;Mohamed and Talal 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, some treatments showed deleterious effects on sperm function. Similarly, after stallion semen thawing [ 41 ], date palm extract exerted a protective effect on sperm motility and acrosome and membrane integrity at a range of concentrations from 20 to 30 mg/mL. On the other hand, some extract concentrations had negative effects on several sperm parameters.…”
Section: Herbal Pharmacognosy and Its Use In Andrologymentioning
confidence: 99%
“…En efecto, varios estudios han mostrado que las yemas de huevo de diferentes especies de aves muestran una variación en sus componentes, lo que resulta en diferentes efectos en el proceso de criopreservación sobre los espermatozoides (Trimeche et al, 1997;Bathgate et al, 2006;Singh et al, 2013). Además, la yema de huevo puede contener metabolitos dañinos y endotoxinas que afectan la viabilidad de los espermatozoides (Vidal et al, 2013), así como hormonas esteroides que reducen la motilidad espermática (El-Sisy et al, 2018). Previos estudios de laboratorio revelan que, mediante eliminación de algunos componentes en la yema de huevo por centrifugación; además de ciertas sustancias en la yema que inhiben la respiración y la motilidad espermática, sugiriendo el reemplazo la yema de huevo entera por la fracción crioprotectora (Amirat et al, 2004).…”
Section: Cuadro 1 Medias (±Eem) Para La Calidad Del Semen Criopreserunclassified
“…De manera particular, en el macho cabrío, existen interacciones negativas entre los fosfolípidos de la yema de huevo y la glándula bulbouretral, esta glándula secreta con el plasma seminal una enzima coagulante de la yema de huevo, la cual cataliza la hidrólisis de la lecitina de la yema de huevo en ácidos grasos y lisolecitina, que son citotóxicos (Ngoma et al, 2016). Por lo anterior, se han utilizado sustitutos de la yema de huevo químicamente definidos sin ser de origen animal (El-Sisy et al, 2018;Gamal et al, 2016), elaborados a base de lecitina de soya y que pueden ser alternativas potenciales para la criopreservación del semen (Akhter et al, 2012).…”
Section: Introductionunclassified